ELECTROCHEMICAL INVESTIGATION OF OCTAETHYL PORPHYRIN IRON(III) CHLORIDE IN THE PRESENCE OF PYRIDINE, IMIDAZOLE AND COLLIDINE: AN APPROACH TO THE ROLE OF PYRIDINE IN THE COUPLED OXIDATION (Journal of Sciences, Islamic Republic of Iran)
Cyclic voltammogram and differential pulse polarograph of octaethyl porphyrin iron(III) chloride in dichloromethane was investigated in the presence of pyridine, imidazole and collidine. Values of E1/2 for FeIII/FeII redox reaction were monitored as a function of axial group concentration, and on the basis of these data, an overall oxidation-reduction and ligand addition scheme was formulated. Addition of pyridine resulted in anodic shift for oxidation wave from –0.16 V to –0.06 V while for imidazole and collidine we observed a cathodic shift.